2007
DOI: 10.1093/carcin/bgm076
|View full text |Cite
|
Sign up to set email alerts
|

Apo-10′-lycopenoic acid inhibits lung cancer cell growth in vitro, and suppresses lung tumorigenesis in the A/J mouse model in vivo

Abstract: High intake of lycopene has been associated with a lower risk of a variety of cancers including lung cancer. We recently showed that lycopene can be converted to apo-10'-lycopenoids [Hu et al. (2006). J. Biol. Chem., 281, 19327-19338] in mammalian tissues both in vitro and in vivo, raising the question of whether apo-10'-lycopenoids have biological activities against lung carcinogenesis. In the present study, we report that apo-10'-lycopenoic acid inhibited the growth of NHBE normal human bronchial epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 50 publications
6
128
0
1
Order By: Relevance
“…The lycopene metabolite, apo-10'-lycopenoic acid, inhibits lung cancer cell growth in vitro and suppress murine lung tumorigenesis in vivo (43). More recently, supraphysiologic concentrations of apo-12'-lycopenal were shown to inhibit androgen-resistant prostate cancer cell growth (10,19).…”
Section: Discussionmentioning
confidence: 99%
“…The lycopene metabolite, apo-10'-lycopenoic acid, inhibits lung cancer cell growth in vitro and suppress murine lung tumorigenesis in vivo (43). More recently, supraphysiologic concentrations of apo-12'-lycopenal were shown to inhibit androgen-resistant prostate cancer cell growth (10,19).…”
Section: Discussionmentioning
confidence: 99%
“…In studies with the lycopene degradation product apo-10'-lycopenoic acid at concentrations from 0.5 to 10 µM, Lian et al [37] observed that the growth of the human non-small cell lung cancer cell line A549 was arrested at the G1/S phase with decreased levels of cyclin E and increased levels of the cell cycle regulatory proteins p21 and p27. Antiproliferative effects of lycopene without details regarding the mechanism of action have also been reported for the human breast cancer cell line MCF-7 [38], rat prostate cancer AT3 cells [39], primary human prostate epithelial cells [40], the human erythroleukemia cell line K562, Raji cells, and human colon cancer HuCC cells [33].…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
“…[14][15][16] Accumulating evidence suggests the potentiality of LP for targeting cancer therapy as an anticancer agent. However, the extreme instability and poor bioavailability of LP may limit its application in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%